Peningkatan Kemampuan Penggunaan Tata Bahasa Baku Pada Remaja Tingkat SMP/MTs Di Gampong Keude Lueng Putu Pidie Jaya - Rahmi, Hayatun; Nofiana S; Nurjannah (Yayasan Sagita Akademia Maju, 2024)
Introducing language to the public, especially teenagers, certainly requires a long process. This is done for the sake of creating the nation's children who understand their language, namely Indonesian. This Community service activity aims to encourage teenagers to understand standard Indonesian grammar and also to improve teenagers' ability to use standard Indonesian. There are three stages used in this community service method, namely the first stage is observation, the second stage is the core activity, namely providing training, and the third stage is the final activity, namely entering the activity evaluation stage. The level of use of varieties of Indonesian by teenagers in the school environment is still relatively low, the level of use of standard Indonesian by teenagers in the family environment is also still low, while the results of diagnostic tests on standard Indonesian grammar skills of teenagers in Keude Lueng Putu gampong are also still low. However, even though teenagers' abilities are still relatively low, this activity can show that teenagers have high enthusiasm for participating in activities and increased competence in answering Indonesian grammar questions that were previously not understood and misused. Therefore, training on standard grammar really needs to be given to teenagers in Gampong Keude Lueng Putu.